ナンキョク ロガンイキ ノ チケイ ケイセイ サヨウ ニ カンスル カンソク ト ジッケン テンボウ ト コンゴ ノ カダイ - 松岡, 憲知; マツオカ, ノリカズ; Matsuoka, Norikazu (1996)
P(論文) 寒冷砂漠という特異な気候地形区に属する南極露岩域では, 岩石の風化・風食, 凍上・斜面特質移動, 構造土の変形などの地形形成作用が種々の手法で計測されてきた。しかし, その多くは地形変化の速度の値を求めることが主目的とされ, 地温・土壌水分・風速などそれらの地形変化を支配する物理的要因との関連は十分には議論されなかった。最近の長期無人観測機器の進歩により, 従来の手動計測では得ることのできなかった, 地形変化の発生時期とそのときの気象・水文条件に関する情報が入手できるようになり, 地形変化の物理的機構が定量的に議論されるようになった。宇宙線照射年代法に基づく露岩の露出年代値の増加により, 観測結果は地形発達の議論にも適用されるようになっている。今後は, 地域間の比較研究を促進するために, 同一の手法による観測や標準試料を用いた実験の実施が望まれる。 This paper aims to review dynamic approaches to geomorphic processes in the Antarctic ice-free areas, most of which lie in the cold desert zone, and to propose for future research. A variety of methodologies have been used to measure rock weathering, wind erosion, frost heave, slope processes and patterned ground formation. Whereas a number of attempts have been made to quantify rates of erosion or mass movements, difficulties in long-term, continuous monitoring have long militated against understanding of the physical processes that control the rates. Recent progress in automated data logging techniques enables us to acquire data on the timing and cause of geomorphic changes. These data, combined with cosmogenic exposure ages, can be applied to the reconstruction of Late Cenozoic landscape evolution. Experimental techniques should be standardized to promote intersite comparisons of morphogenetic environments. departmental bulletin paper